2007
DOI: 10.1074/jbc.m700632200
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic RNAi Depletion of Claudin-16 and the Renal Handling of Magnesium

Abstract: Tight junctions play a key role in mediating paracellular ion reabsorption in the kidney. Familial hypomagnesemia with hypercalciuria and nephrocalcinosis (FHHNC) is a human disorder caused by mutations in the tight junction protein claudin-16. However, the molecular mechanisms underlining the renal handling of magnesium and its dysfunction causing FHHNC are unknown. Here we show that claudin-16 plays a key role in maintaining the paracellular cation selectivity of the thick ascending limbs of the nephron. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
166
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(179 citation statements)
references
References 42 publications
11
166
2
Order By: Relevance
“…This is supported by recent analysis of claudin-16 RNAi knockdown mice, which reproduce the human phenotype of renal Ca 2ϩ and Mg 2ϩ wasting and nephrocalcinosis (46). In studies using in vitro perfused TALH tubules from these mice, the P Na /P Cl ratio was found to be decreased twofold with no change in P Na /P Mg or transtubular resistance, suggesting that the major defect is a decrease in P Na in the TALH.…”
Section: Role Of Claudins In Human Diseasessupporting
confidence: 54%
See 1 more Smart Citation
“…This is supported by recent analysis of claudin-16 RNAi knockdown mice, which reproduce the human phenotype of renal Ca 2ϩ and Mg 2ϩ wasting and nephrocalcinosis (46). In studies using in vitro perfused TALH tubules from these mice, the P Na /P Cl ratio was found to be decreased twofold with no change in P Na /P Mg or transtubular resistance, suggesting that the major defect is a decrease in P Na in the TALH.…”
Section: Role Of Claudins In Human Diseasessupporting
confidence: 54%
“…The second model, put forward by Goodenough and colleagues (46), is that claudin-16 really functions primarily as a paracellular Na ϩ pore. This is supported by recent analysis of claudin-16 RNAi knockdown mice, which reproduce the human phenotype of renal Ca 2ϩ and Mg 2ϩ wasting and nephrocalcinosis (46).…”
Section: Role Of Claudins In Human Diseasesmentioning
confidence: 99%
“…We previously described a CLDN16 KD animal model that recapitulates human FHHNC phenotypes (17). Human mutations in CLDN19 also result in FHHNC (15).…”
Section: Loss Of Cldn19 Resulted In Renal Wasting Of Magnesium and Camentioning
confidence: 99%
“…S2). These sequences were then cloned into the pUG-U6 vector (17), upstream of the red fluorescent protein (''cherry'') driven by the ubiquitin-C promoter. After testing of the lentivirus in cultured mouse TAL cells, transgenic mouse lines were generated by perivitelline injection of virus to fertilized mouse embryos.…”
Section: Loss Of Cldn19 Resulted In Renal Wasting Of Magnesium and Camentioning
confidence: 99%
See 1 more Smart Citation